2022
DOI: 10.1038/s41419-022-05004-3
|View full text |Cite
|
Sign up to set email alerts
|

S100A11 activates the pentose phosphate pathway to induce malignant biological behaviour of pancreatic ductal adenocarcinoma

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is one of the most refractory malignancies and has a poor prognosis. In recent years, increasing evidence has shown that an imbalance of metabolism may contribute to unrestricted pancreatic tumour progression and that the pentose phosphate pathway (PPP) plays a pivotal role in cellular metabolism. S100A11 has been shown to regulate multiple biological functions related to the progression and metastasis of various cancer types. However, the exact mechanisms and prognostic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…The inhibition of glucose 6-phosphate dehydrogenase (G6PD) has been shown to reduce omental metastasis of ovarian cancer cells, thus suggesting a role of PPP in peritoneal metastasis of ovarian cancers [51,52]. A similar role of PPP pathway intermediates has been observed in peritoneal metastasis involving gastric, pancreatic, and colorectal cancers [49,53,54]. It has also been observed that the key enzymes of PPP such as G6PD, transaldolase, and transketolase are upregulated in pleural mesothelioma cell lines, which has a certain degree of similarity with the peritoneal mesothelioma [55].…”
Section: Glucose Metabolismmentioning
confidence: 99%
“…The inhibition of glucose 6-phosphate dehydrogenase (G6PD) has been shown to reduce omental metastasis of ovarian cancer cells, thus suggesting a role of PPP in peritoneal metastasis of ovarian cancers [51,52]. A similar role of PPP pathway intermediates has been observed in peritoneal metastasis involving gastric, pancreatic, and colorectal cancers [49,53,54]. It has also been observed that the key enzymes of PPP such as G6PD, transaldolase, and transketolase are upregulated in pleural mesothelioma cell lines, which has a certain degree of similarity with the peritoneal mesothelioma [55].…”
Section: Glucose Metabolismmentioning
confidence: 99%
“…Increased expression of the calcium-binding protein S100A11 in PDAC promotes the loading of H3K4me3 onto the TKT promoter, enhancing the PPP by increasing TKT levels and leading to worse clinical prognosis and disease progression. This suggests that S100A11 may be a possible therapeutic target ( Zeng et al, 2022 ). PPP is a branch of glycolysis.…”
Section: Alterations In Glucose Metabolismmentioning
confidence: 99%
“…S100A11 is a member of the S100 protein family and has high homology with calmodulin and EF-hand calcium-binding proteins, which promotes tumor progression through cell proliferation, metastasis, angiogenesis and immune evasion. Recent studies reported that S100A11 was an oncogene in pancreatic ductal adenocarcinoma [1,2], glioma [3][4][5], colorectal cancer [6], breast cancer [7], lung cancer [8], thyroid cancer [9], and gastric cancer [10]. However, the biological function of S100A11 in the tumor microenvironment (TME) has been rarely reported.…”
Section: Introductionmentioning
confidence: 99%